2016
DOI: 10.1007/s00330-016-4611-0
|View full text |Cite
|
Sign up to set email alerts
|

Substantia nigra fractional anisotropy is not a diagnostic biomarker of Parkinson’s disease: A diagnostic performance study and meta-analysis

Abstract: • SN-FA appears insufficiently sensitive and specific to diagnose PD. • Radiologists must be careful when translating mean group results to clinical practice. • Imaging protocol and analysis standardization is necessary for developing reproducible quantitative biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 44 publications
1
16
1
Order By: Relevance
“…The authors proposed that FA measurements in the caudal and lateral subregions of the SN, presumably coinciding with the histological described SNc location (ROI subdivision Type B1), have the best diagnostic value for PD. However, eight subsequent studies with the same SN subdivision (subdivision Type B) reported discrepant findings: two studies (13, 132) likely replicated the findings of FA reduction in the dorsal lateral sub-region of the SN in PD; five other studies (7,8,55,104,131) found no significant FA differences between PD and HC in any SN sub-region; and one (130) reported elevated FA in all the SN sub-regions in PD. Technical difficulties outlining the sub-regions may explain these discrepant findings.…”
Section: Dti Changes In Sn and Sn Subdivisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed that FA measurements in the caudal and lateral subregions of the SN, presumably coinciding with the histological described SNc location (ROI subdivision Type B1), have the best diagnostic value for PD. However, eight subsequent studies with the same SN subdivision (subdivision Type B) reported discrepant findings: two studies (13, 132) likely replicated the findings of FA reduction in the dorsal lateral sub-region of the SN in PD; five other studies (7,8,55,104,131) found no significant FA differences between PD and HC in any SN sub-region; and one (130) reported elevated FA in all the SN sub-regions in PD. Technical difficulties outlining the sub-regions may explain these discrepant findings.…”
Section: Dti Changes In Sn and Sn Subdivisionsmentioning
confidence: 99%
“…Table 4 lists 32 independent studies that analyzed DTI in the total SN area and SN sub-regions in order to identify substantial DTI alterations in patients with PD. These studies were included in four previous meta-analyses and reviews (104,131,135,136 Table 4) is sensitive to capture the dopamine loss in PD. Molecular and neuropathological studies (137) of PD have highlighted that progressive loss of dopaminergic neurons is primarily involved in the pars compacta (SNc), which contains rich pigment neuromelanin formed by dopaminergic neurons, and lies in the inferior and posterior part of the SN, in contrast to the pars reticulata (SNr), which lies lateral to the SNc.…”
Section: Dti Changes In Sn and Sn Subdivisionsmentioning
confidence: 99%
“…Metrics changes in SN are controversial. Previous studies have demonstrated conflicting observations in SN, such as an increased (Van Camp et al, 2009;Wang et al, 2011;Lenfeldt et al, 2015), decreased (Boska et al, 2007;Vaillancourt et al, 2009;Langley et al, 2016;Loane et al, 2016), or unaltered (Schuff et al, 2015;Hirata et al, 2017;Pelizzari et al, 2019) FA in PD patients. Our study showed an increased FA in SN in PD patients, which was consistent with some of the previous studies (Van Camp et al, 2009;Wang et al, 2011;Lenfeldt et al, 2015), but inconsistent with other studies (Boska et al, 2007;Vaillancourt et al, 2009;Langley et al, 2016;Loane et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…There are conflicting findings concerning the usefulness of SN DTI metrics in PD diagnosis, according to recent metaanalyses (45)(46)(47) and recent voxelwise analysis-based studies concerning the whole SN (48)(49)(50). Fractional Anisotropy (FA) in the posterior part seems to be the most discriminant feature (51,52).…”
Section: Diffusion Weighted Imaging Diffusion Tensor Imaging (Dti)mentioning
confidence: 99%